Argyrogrammana Strand (Lepidoptera: Riodinidae) from Parque Nacional da Serra do Divisor, Acre, Brazil, with the description of four new species - Dolibaina, Diego Rodrigo; Dias, Fernando Maia Silva; Mielke, Olaf Hermann Hendrik; Casagrande, Mirna Martins (Zootaxa, 2015)
The species of Argyrogrammana Strand, 1932 collected at the Parque Nacional da Serra do Divisor, Acre, Brazil (PNSD) are listed and detailed with behavioral notes. In total, 17 species were recorded, including 13 new records for Brazil (marked with an asterisk): A. alstonii (Smart, 1979)*, A. nurtia ludibunda Brévignon & Gallard, 1995*, A. pulchra (Talbot, 1929)*, A. bonita Hall & Willmott, 1995*, A. amalfreda (Staudinger, [1877])*, A. physis phyton (Stichel, 1911), A. halli Dolibaina & Dias, sp. nov.*, A. celata Hall & Willmott, 1995*, A. gallardi Dolibaina & Dias, sp. nov.*, A. aparamilla Hall & Willmott, 1995*, A. praestigiosa (Stichel, 1929), A. johannismarci Brévignon, 1995*, A. brevignoni Dolibaina & Dias, sp. nov.*, A. rameli (Stichel, 1930), A. willmotti Dolibaina & Dias, sp. nov.*, A. iracyi P. Jauffret & J. Jauffret, 2007 and A. saulensis tunari Gallard, 2008, comb. nov.*. Four new species are described, two from “amalfreda complex”: A. halli Dolibaina & Dias, sp. nov. and A. gallardi Dolibaina & Dias, sp. nov.; one from “trochilia complex”: A. brevignoni Dolibaina & Dias, sp. nov.; and one from “stilbe complex”: A. willmotti Dolibaina & Dias, sp. nov. Argyrogrammana iracyi saulensis Gallard, 2008 is recognized as a valid species, A. saulensis saulensis, stat. nov., and a new combination is proposed to A. saulensis tunari Gallard, 2008, comb. nov. The females of A. iracyi P. Jauffret & J. Jauffret, 2007 and A. saulensis tunari are recognized and figured for the first time. The taxonomy of the species found at the PNSD is discussed and adults are figured, including illustrations of the genitalia.